Synthesis, Spectroscopic Studies of Some Transition Metal Complexes of Schiff Bases Derived from Diamine Compounds - Fatima F. Hassan (University of Thi-Qar Journal of Science, 2019)
The present work include preparation of three ligands (Schiff base) by condensation of (Phthaldialdehyde) with1,3-diamino-2-propanol) to give ligands (L) L: (1Z,6Z)-4,5-dihydro -3H-2,6-benzodiazonin-4-olo characterize the structure of prepared ligands and their complexes, elemental analysis (C.H.N),Infrared Spectroscopy (IR), Nuclear Magnetic Resonance Spectroscopy(1H-NMR),Mass Spectra and Molar conductivityechniques were applied . The results showed that:- The complexes of [Co(III) and Cr(III)] for ligand have shown octahedral configuration.- Complexes of [ Ni(II)] with ligands have shown tetrahedral configuration.